Nanoparticle-mediated oxidative stress monitoring - Lima, Thania Rios Rossi [UNESP]; Nunes, Rony; Pereira, Lilian Cristina [UNESP] (Elsevier, 2019)
Free radicals are unstable atoms or molecules that can be not only generated under physiologic conditions but also induced by many exogenous compounds. They interact with many molecular and cellular targets and may cause adverse effects owing to oxidative stress, i.e., an imbalance between the generation of oxidizing compounds and the performance of antioxidant defense systems. Nanoparticles are a broad class of materials that include particulate matter ranging in size from 1 to 100 nm and that are applied in numerous fields such as medicine, manufacture, and sustainable energy. These materials have been monitored for efficacy and safety, including around induction of oxidative stress.
Keywords: Mitochondria; Nanoparticles; Nanotechnology; Oxidative stress; Rons production